In Vivo Effects of Bothrops jararaca Venom on Metabolic Profile and on Muscle Protein Metabolism in Rats - Goncalves, Dawit A. P.; Silva, Erico V. C. M. [UNESP]; Graca, Flavia A.; Lira, Eduardo C.; Zanon, Neusa M.; Mendes, Gloria E.; Burdmann, Emmanuel A.; Migliorini, Renato H.; Kettelhut, Isis C.; Navegantes, Luiz C. C. (Amer Soc Trop Med & Hygiene, 2008)
This study investigated the in vivo effects of the Bothrops Jararaca venom (BjV) on general metabolic profile and, specifically. oil muscle protein metabolism in rats. The crude venom (0.4 mg/kg body weight, IV) was infused in awake rats, and plasma activity of enzymes and metabolites levels were determined after 1, 2, 3, and 4 hours. BjV increased urea, lactate, and activities of creatine kinase. lactate dehydrogenase. and aspartate aminotransferase after 4 hours. The content of liver glycogen was reduced by BjV. Protein metabolism was evaluated by means of microdialysis technique and in isolated muscles. BjV induced increase in the muscle interstitial-arterial tyrosine concentration difference. indicating a high protein catabolism. The myotoxicity induced by this venom is associated with reduction of protein synthesis and increase in rates of overall proteolysis, which was accompanied by activation of lysosomal and ubiquitin-proteasome systems without changes in protein levels of cathepsins and ubiquitin-protein conjugates.